DEVELOPING SPEAKING COMPETENCE AND THE TECHNIQUES ON TEACHING SPEAKING IN SMPN 1 KALASAN - Debora Harsono (JURNAL TAHURI, 2018)
This research aims are to investigate the level speaking competence of the eight grade students of SMPN-1 Kalasan and the techniques that the teachers apply to develop students speaking competence. The design of this research is a case study. To achieve the credibility of data for this research, a sequence of processes of data collection was conducted, namely speaking test, observation, field note, interview and documentation. The findings of this research consist of two parts. First, the students have developed the speaking ability. The student’s ability in English progressed from fair to good level,and then from good to excellent level, especially in pronunciation, fluency, and vocabulary. Eventhough the students have problems in grammar, they achieve progress in the three aspects, such as pronunciation, fluency and vocabulary. The progress of the students is mainly due to the second finding. Second, the six teaching techniques that the teachers apply are imitating, repeating, practicing, role playing, making dialogue and questions—answers process. These techniques have the benefit of improving student’s ability in English. Before using these teaching techniques, it is found that the students show the fair level. After applying these techniques, the student achieve the progress in three aspects. These techniques have proved to be beneficial to the students in improving their English speaking competence.